Sikap dan Perilaku Aparatur dalam Melaksanakan Anggaran Pendapatan dan Belanja Daerah Butas - Hasiara, La Ode (Jurnal Aplikasi Manajemen, 2013)
The objective of research is to describe the attitude and behavior of the officer in the implementationof the local revenue and expense budget in Butas Regency. This implementation of the local revenueand expense budget begins from the setting of this budget in KUA and PPAS because both agencies areacting as the base organizations in driving the wheel of local government. Research method is qualitativewith grounded theory approach. This theory involves systematic procedures such as analysis and discussion.Result of research is subjected to the data categorization based on three stages, (1) open coding, (2)axial coding, and (3) selective coding. These three categories will show up other name representing theprevious data category name but principally may not eliminate the significance of data in the previousname. Result of research indicates some attitudes and behaviors of the officer in the implementation of thelocal revenue and expense budget (APBD). These attitudes are related to the behavior shown amonggovernmental officers, in which passive and active attitudes are estimated. Both attitudes produce submissive,compliance and obedient behaviors in the implementation of the local revenue and expense budget.